Pressure‐Tailored Band Engineering for Significant Enhancements in the Photoelectric Performance of CsI3 in the Optical Communication Waveband. (9th November 2021) - Li, Zonglun; Li, Quanjun; Li, Haiyan; Yue, Lei; Zhao, Dianlong; Tian, Fuyu; Dong, Qing; Zhang, Xueting; Jin, Xilian; Zhang, Lijun; Liu, Ran; Liu, Bingbing
Abstract: The bandgap and type of optical transition are key factors in determining the functionalities and applications of photoelectric materials. However, it is extremely difficult to modulate the bandgap and indirect‐direct bandgap transition for most materials. This study reports significant enhancements in photocurrents and an extended detection bandwidth resulting from pressure‐regulated indirect–direct bandgap transition in hypervalent CsI3 . Furthermore, this study achieves an increase in the photocurrent by almost five orders of magnitude under visible‐light illumination. Impressively, the detection band‐edge shows a successive redshift from visible light to 1650 nm (optical communication waveband) upon compression. And high pressure is conducive to CsI3 operating at an ultralow bias input. Extensive high‐pressure spectroscopy analyses and theoretical calculations suggest that changes in the photoelectric properties of CsI3 are associated with enhanced I–I interactions along the quasi‐endless linear chain directions under compression. These findings offer an effective band engineering strategy for achieving broadband spectral response and high gains with an ultralow bias in photoelectric detectors. Abstract : This study achieves a significantly increased photocurrent by almost five orders of magnitude under visible light illumination and an extension of the spectral response range to the optical communication waveband (1650 nm) in CsI3 via pressure‐tailored band engineering. These findings provide new insights for designing wide‐range photosensitive, high‐gain, and operable‐at‐ultralow‐bias‐input photoelectric functional materials.